2012
DOI: 10.1089/end.2011.0352
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Single Incision Laparoscopic Totally Extraperitoneal and Laparoscopic Totally Extraperitoneal Inguinal Hernia Repair: Initial Experience

Abstract: In our experience, LESS-TEP is a safe and feasible procedure with a short learning curve. In all analyzed parameters, it is comparable to conventional LAP-TEP. Further studies that compare LESS-TEP and conventional multiport LAP-TEP repairs with long-term follow-up evaluation are needed to confirm the initial experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 12 publications
1
70
0
Order By: Relevance
“…On further scrutiny, 16 articles 15,19,22,[35][36][37][38][39][40][41][42][43][44][45][46][47] were used in our literature review and 3 studies comparing LESS TEP with LAP TEP were found to have useful data for the summative outcome. One study commented on a previous report.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…On further scrutiny, 16 articles 15,19,22,[35][36][37][38][39][40][41][42][43][44][45][46][47] were used in our literature review and 3 studies comparing LESS TEP with LAP TEP were found to have useful data for the summative outcome. One study commented on a previous report.…”
Section: Resultsmentioning
confidence: 99%
“…One study commented on a previous report. 37 Three studies 22,40,45 compared LESS TEP with LAP TEP and were combined to produce a summative outcome. A flow chart of the literature search according to PRISMA guidelines 48 is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations